STUDENTS’ DIFFICULTIES IN ENGLISH SPEAKING LESSON AT THE ELEVENTH GRADE OF STATE SENIOR HIGH SCHOOL 04 MUKO-MUKO - Fenta Zelva Leoni; Kasmaini; Azhar Aziz Lubis (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
This research aimed to describe the students’ difficulties encountered by the eleventh-grade students of State Senior High School 04 Muko-Muko in English Speaking Lesson and to describe the factors causing the difficulties in English Speaking Lesson at the eleventh grade of State Senior High School 04 Muko-Muko. This research used mix method research design. The subject of this research was eleventh grade students at State Senior High School 04 Muko-Muko. The sample of the research was 31 students for questionnaires and 10 students for interview. The instruments of this research were questionnaire adapted from Rahayu (2020) and interview. The researcher analyzed the data by by finding the percentage of each question item in questionnaire while interview data was analyzed by data reduction, data display, and drawing conclusion. This study found two findings. First, the result showed that there were five psychological difficulties encountered by the eleventh grade students of State Senior High School 04 Muko-Muko in English Speaking Lesson, namely lack of motivation, anxiety, shyness, fear of mistakes, and lack of confidence. Second, based on five psychological difficulties, there are several factors causing namely no awareness to learn english, no interest of English, no knowledge of the importance of English, students’ low English skill in vocabulary and pronunciation, friends’ negative responses, teacher’s bad responses, and students’ terrible belief in their English skill. To sum up, the next study is recommended to find the strategies to overcome the students’ difficulties in English speaking lesson.